2003
DOI: 10.1007/bf02914501
|View full text |Cite
|
Sign up to set email alerts
|

Tibial shaft fractures treated with the AO unreamed tibial nail

Abstract: The AO UTN does have a high complication rate and, should it be used, we feel that early dynamisation or exchange nailing be considered to hasten union and prevent screw breakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…There were two malunions in Kutty et. al's research of 45 patients with reamed interlock nails; in contrast, our findings indicated that union occurred in 90-150 days with a mean of 110.68 days and no malunion, which is quite comparable to other studies' findings [14]. In our investigation, we used a nail after reaming the canal to finish the job.…”
Section: Discussionsupporting
confidence: 84%
“…There were two malunions in Kutty et. al's research of 45 patients with reamed interlock nails; in contrast, our findings indicated that union occurred in 90-150 days with a mean of 110.68 days and no malunion, which is quite comparable to other studies' findings [14]. In our investigation, we used a nail after reaming the canal to finish the job.…”
Section: Discussionsupporting
confidence: 84%
“…Intramedullary nailing is considered to be the optimum treatment for fractures of the long bones of the lower limbs and various studies have been published describing the functional outcome of both reamed and unreamed nailing. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Several complications have been described including infection, 2,13,14 compartment syndrome, [16][17][18][19][20][21][22][23][24][25][26][27][28][29] deep-vein thrombosis, [30][31][32] thermal necrosis of the bone with alteration of its endosteal architecture, [33][34][35][36][37][38][39][40] failure of the metalwork 16,20,22,23,27 and malunion and nonunion of the f...…”
mentioning
confidence: 99%
“…In unreamed nailing, there is less risk of fat embolism and several studies suggest better preservation and more-rapid recovery of the intraosseous blood supply after insertion of a small-diameter nail without reaming [17][18][19][20][21][22] . In contrast, studies by Blachut et al 23 and Court Brown et al 24 seem to indicate that nonunion occurs more frequently with unreamed nailing 17,25,26 .…”
Section: Discussionmentioning
confidence: 99%